USDA News Release Usage Survey; The Al Newsletter as Marketing Communications Tool ; Missouri Farm News Service Usage Survey - Max B. Heppner; James C. Dohner; Evan Davies; Joseph J. Marks (Journal of Applied Communications, 1981)
Three Research Briefs: USDA News Release Usage Survey; The Al Newsletter as Marketing Communications Tool ; Missouri Farm News Service Usage Survey